1998
DOI: 10.1212/wnl.50.2.351
|View full text |Cite
|
Sign up to set email alerts
|

Object and action naming in Alzheimer's disease and frontotemporal dementia

Abstract: To assess noun and verb processing in different dementia types, we tested object and action naming in three groups of subjects: probable Alzheimer's disease (AD) with mild to moderate dementia; age- and education-matched normal subjects; and a group of frontotemporal dementia (FTD) patients. AD and FTD patients were impaired in naming compared with control subjects; action naming was more severely impaired. However, the discrepancy between object and action naming was significantly greater in FTD than in AD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
1
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(108 citation statements)
references
References 0 publications
6
95
1
6
Order By: Relevance
“…Furthermore, Bak et al [2], Bak and Hodges [3] recently reported that bilateral lesions of frontal areas, as present in motor neuron disease, can also have specific effects on the processing of action verbs. In addition, Cappa et al [10] found most pronounced deficits in fronto-temporal dementia. These data are consistent with the view that the frontal cortices on the left and right both support the action associations of words, thereby facilitating word processing.…”
Section: Comparison Of the Present Results With Earlier Findingsmentioning
confidence: 95%
“…Furthermore, Bak et al [2], Bak and Hodges [3] recently reported that bilateral lesions of frontal areas, as present in motor neuron disease, can also have specific effects on the processing of action verbs. In addition, Cappa et al [10] found most pronounced deficits in fronto-temporal dementia. These data are consistent with the view that the frontal cortices on the left and right both support the action associations of words, thereby facilitating word processing.…”
Section: Comparison Of the Present Results With Earlier Findingsmentioning
confidence: 95%
“…A double dissociation may be postulated between PD patients and those exhibiting selective object-word deficits with relative preservation of action words and action semantics subsequent to posterior atrophy, as observed in Alzheimer's disease [36] and semantic dementia [37,38]. Furthermore, differential activations of frontal/prefrontal regions for verbs, and middle/posterior temporal regions for nouns, have been reported in neuroimaging studies with neurotypical native speakers of English [39,40], German [41], Italian [42], and Japanese [43].…”
Section: Action-language Impairments In Parkinson's Diseasementioning
confidence: 93%
“…'s specific problems with verb production may stem from damage to part of the left midfrontal gyrus supe-rior to Broca's area, corresponding to Brodmann area 9. Lesions in this region have been linked to verb retrieval deficits in patients with stroke and neurodegenerative diseases [1,8,13], and neuroimaging studies have shown that left prefrontal/premotor cortex is recruited (along with other parts of the brain) more heavily during verb naming than noun naming [36,38]. However, the significance of this association has been controversial.…”
Section: Neuroanatomical Correlates Of Grammatical Processingmentioning
confidence: 99%